2008
DOI: 10.1163/156805808x333901
|View full text |Cite
|
Sign up to set email alerts
|

'He Is He, and I Am I': Individual and Collective among China's Rural Elderly

Abstract: China's rural elderly strongly feel the tension between the life patterns they had expected to follow and the risks and possibilities presented by a more dynamic and individualised society. This paper discusses how the elderly react to the rapid changes in intergenerational relations. The focus is on their strategies towards the two most common types of living arrangements during old age: maintaining an independent household, and living with a son's family. Earlier generations of elderly perceived cohabitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Only the childless elderly are eligible for state‐provided “five guarantees” benefits, which cover the basic livelihood needs of food, housing, clothing, and health care as well as burial costs; which are provided at the lowest subsistence level (Thogersen & Ni, , p. 13). Most rural elderly receive neither pensions nor health benefits, and so are forced to rely on their adult children for financial support when they lose their ability to earn an income.…”
Section: Absence Of Social Welfare System and The Persistence Of Intementioning
confidence: 99%
See 3 more Smart Citations
“…Only the childless elderly are eligible for state‐provided “five guarantees” benefits, which cover the basic livelihood needs of food, housing, clothing, and health care as well as burial costs; which are provided at the lowest subsistence level (Thogersen & Ni, , p. 13). Most rural elderly receive neither pensions nor health benefits, and so are forced to rely on their adult children for financial support when they lose their ability to earn an income.…”
Section: Absence Of Social Welfare System and The Persistence Of Intementioning
confidence: 99%
“…Health care has become an issue for many elderly since their medical costs are only partially covered due to work place reforms as a result of withdrawal or reduction of state subsidies since 1990s (Ikels, , p. 312). Moreover, both urban and rural elderly people are left with no option but to rely on their family for care when they become physically dependent (Liang & Gu, ; Thogersen & Ni, , p. 31; Whyte, ). An online survey conducted in early October 2012 found that “about 90 percent of the public was seriously concerned about their quality of life in old age” (Yan, , p. A7).…”
Section: Absence Of Social Welfare System and The Persistence Of Intementioning
confidence: 99%
See 2 more Smart Citations
“…For the elderly, cultural values of work are disappearing, so that they are becoming "useless" persons. Some rural elderly actively restructure their social and civic ties for arranging independent daily life as long as they can still afford, in articulating the role of individual choice and personal freedom (Zhang 2004;Thøgersen and Ni 2008), while others claim support provisions on the basis of pursuing fairness. In fact, they are the two sides of the same coin.…”
Section: Fairness and Insecuritymentioning
confidence: 99%